Mycophenolic acid, the active form of mycophenolate mofetil, interferes with IRF7 nuclear translocation and type I IFN production by plasmacytoid dendritic cells - Minoru Shigesaka; Tomoki Ito; Muneo Inaba; Kai Imai; Hideki Yamanaka; Yoshiko Azuma; Akihiro Tanaka; Hideki Amuro; Tohru Nishizawa; Yonsu Son; Atsushi Satake; Yoshio Ozaki; et al. (Arthritis Research & Therapy, 2020)
Abstract Background Both humoral and cellular immune mechanisms are involved in the onset and progression of autoimmune responses in systemic lupus erythematosus (SLE). Plasmacytoid dendritic cells (pDCs) play a central role in the pathogenesis of SLE via the dysregulation of type I interferon (IFN) production; these cells act together with activated myeloid DCs (mDCs) to amplify the vicious pathogenic spiral of autoimmune disorders. Therefore, control of aberrant DC activation in SLE may provide an alternative treatment strategy against this disease. Mycophenolate mofetil (MMF), which has been used to treat lupus nephritis, specifically blocks the proliferation of B and T lymphocytes via inhibition of inosine-5-monophosphate dehydrogenase. Here, we focus on the effects of MMF in targeting DC functions, especially the IFN response of pDCs. Methods We isolated human blood pDCs and mDCs by flow cytometry and examined the effect of mycophenolic acid (MPA), which is a metabolic product of MMF, on the toll-like receptor (TLR) ligand response of DC subsets. Additionally, we cultured pDCs with serum from SLE patients in the presence or absence of MPA and then examined the inhibitory function of MPA on SLE serum-induced IFN-α production. Results We found that treatment with 1−10 μM of MPA (covering the clinical trough plasma concentration range) dose-dependently downregulated the expression of CD80 and CD86 on mDCs (but not pDCs) without inducing apoptosis, in response to R848 or CpG-ODN, respectively. Notably, in pDCs, MPA significantly suppressed IFN-α production with IRF7 nuclear translocation and repressed the AKT activity. In addition, MPA inhibited IL-12 production with STAT4 expression in mDCs. We further identified that MPA had an inhibitory effect on SLE serum-induced IFN-α production by pDCs. Conclusions Our data suggest that MPA can interrupt the vicious pathogenic spiral of autoimmune disorders by regulating the function of DC subsets. This work unveiled a novel mechanism for the therapeutic ability of MMF against SLE.